A Study of Parallel Implicit and Explicit Information Processing in Patients With Obsessive-Compulsive Disorder. - Deckersbach, Thilo; Savage, Cary R.; Curran, Tim (American Journal of Psychiatry, 2002)
Objective: This study examined implicit sequence learning in patients with obsessive-compulsive disorder (OCD) under dualtask conditions. Frontal-striatal networks support implicit learning and are implicated in the pathophysiology of OCD. Neuroimaging data suggest that during implicit learning. OCD patients use neural systems normally active during explicit learning to compensate for striatal dysfunction. Method: The authors examined implicit sequence learning in 25 OCD patients and 25 healthy comparison subjects using a dual-task paradigm, with subjects simultaneously engaged in an explicit memory task and an implicit learning task. They predicted that implicit learning in OCD subjects would be disrupted because concurrent explicit information-processing demands would prevent use of compensatory processes. Results: OCD patients failed to show evidence of implicit learning and exhibited a significant deficit in comparison with healthy subjects. Conclusions: These results are consistent with the hypothesis that concurrent explicit and implicit information-processing demands interfere with implicit learning in OCD patients. Reprinted by permission of the publisher.